Ilmu Kawruh Bejo Ki Ageng Suryamentaram - A. Pratisto Trinarso (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
This paper wants to present the philosophy of Ki Ageng Suryamentaram, namely the science of Kawruh Bejo. As a thought, kawruh bejo is knowledge that can be understood not only through the effort to know rationally but it is knowledge that can only be achieved through process of experiencing, abstracting and an¬alyzing experience. As knowledge, the knowledge of kawruh bejo is not only conveyed in terms of understanding, but also as a guide for people who want to have the ability to control themselves and thus reach bejo or happiness in their life.